2018
DOI: 10.3390/en11113114
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Measurement of Oil and Water Distributions in Spontaneous Imbibition Process in Tight Oil Reservoirs

Abstract: Spontaneous imbibition of water into tight oil reservoirs is considered an effective way to improve tight oil recovery. We have combined testing techniques such as nuclear magnetic resonance, mercury injection capillary pressure, and magnetic resonance imaging to reveal the distribution characteristics of oil and water during the spontaneous imbibition process of tight sandstone reservoir. The experimental results were used to describe the dynamic process of oil–water distribution at the microscopic scale. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For example, because of its high velocity, interlayer flow could play a critical role in moisture transport in soils and water uptake by plants, especially in a semiarid or arid region, where a large fraction of water is expected to be retained in clay interlayers. In addition, the molecular-level understanding of water transport in nanometer or sub-nanometer hydrophilic channels obtained in this work may also shed light on issues related to water imbibition or its release during unconventional oil/gas production . The classical Washburn equation suggests that the imbibition of liquid in horizontal channels is a diffusive process .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, because of its high velocity, interlayer flow could play a critical role in moisture transport in soils and water uptake by plants, especially in a semiarid or arid region, where a large fraction of water is expected to be retained in clay interlayers. In addition, the molecular-level understanding of water transport in nanometer or sub-nanometer hydrophilic channels obtained in this work may also shed light on issues related to water imbibition or its release during unconventional oil/gas production . The classical Washburn equation suggests that the imbibition of liquid in horizontal channels is a diffusive process .…”
Section: Discussionmentioning
confidence: 77%
“…In addition, the molecular-level understanding of water transport in nanometer or sub-nanometer hydrophilic channels obtained in this work may also shed light on issues related to water imbibition or its release during unconventional oil/gas production. 52 The classical Washburn equation suggests that the imbibition of liquid in horizontal channels is a diffusive process. 53 Owing to a possible occurrence of clay interlayer flow, the rate of water imbibition or its release could be much faster than that predicted from classical approaches.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The complex pore structure of the core and oil−water distribution make it difficult to form a long-path SIP, which can lead to a decrease in the rate of SI. 62 The different regions of the SI are illustrated in Figure 10.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is consistent with the description of the T 2 spectral distribution. According to the methods of Lai et al and Nie and Chen and Zhu et al, , in this study, the shale pores are divided into three types, as shown in Table , and pore volumes at different scales, as shown in Table . The volume ratios of the micropores, mesopores, and macropores are 59.05, 31.64, and 9.31%, respectively.…”
Section: Resultsmentioning
confidence: 99%